If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+2(7w-2)=-5(2w-2)+6
We move all terms to the left:
2+2(7w-2)-(-5(2w-2)+6)=0
We multiply parentheses
14w-(-5(2w-2)+6)-4+2=0
We calculate terms in parentheses: -(-5(2w-2)+6), so:We add all the numbers together, and all the variables
-5(2w-2)+6
We multiply parentheses
-10w+10+6
We add all the numbers together, and all the variables
-10w+16
Back to the equation:
-(-10w+16)
14w-(-10w+16)-2=0
We get rid of parentheses
14w+10w-16-2=0
We add all the numbers together, and all the variables
24w-18=0
We move all terms containing w to the left, all other terms to the right
24w=18
w=18/24
w=3/4
| 7(6-4n)=-18+2n | | -2(-2w+4)-6w=4(w-4)-6 | | 1x+28=-3x+60 | | (3-1)(1+x)(-2)=2x | | 1x+1=5x+5 | | 7c−4c+c−c=12 | | | | -4(u+3)=-3(4u-1)+2u | | c2+11c+30=0 | | 1x-1=2x+1 | | 16^(3x)=8^x+6) | | 11/7b=4 | | y^2+11y-196=0 | | 7x+44=9(x+4) | | 7(w+3)=2w+26 | | 3x+1.4=2.9 | | 0=0.03x(x-100) | | 2w-2=4(w+4) | | 1x-2=3x+12 | | 25/12=x/12 | | 2x-2=1x+7 | | 26=7(v+6)-5v | | 15+x/3=12 | | -34=6(y-8)-4y | | 1x+18=5x+6 | | | | 4=3w+4(w+8) | | 216+43.2=x | | 5x+19=1x+7 | | 4/13=2b/13=6b/26 | | -11+x/11=-13 | | y/4=7/17 |